Meningkatkan Ekonomi Keluarga Dalam UMKM Rumah Tangga Melalui Pengolahan Sabun Cuci Piring Bagi Masyarkat Desa Besar Ii Terjun - Nicole Theo Fany (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Independent Community Service Program (KKN) implemented in Desa Besar II Terjun, Pantai Cermin District, Serdang Bedagai Regency, aims to increase the capacity of Micro, Small, and Medium Enterprises (MSMEs) through product and marketing innovation. This program focuses on developing MSME products, such as making dishwashing soap, as well as introducing simple marketing techniques, such as using logos and banners for product branding. The method used in this program is a participatory approach, which involves the community in outreach activities, training, and direct mentoring. The results of this activity show that the participating MSMEs are able to apply the product innovations taught, such as developing variations of dishwashing soap products with more attractive packaging. In addition, marketing training increases MSME awareness of the importance of branding in attracting consumer attention, as evidenced by the increase in sales of several products after the use of logos and banners. However, several challenges are still faced, especially in terms of limited access to raw materials and mastery of digital marketing techniques. This program has a positive impact on the development of MSMEs in Desa Besar II Terjun, although there are time constraints in implementation and mentoring. Therefore, further assistance and collaboration with the local government are needed to ensure the sustainability of the results achieved. This activity is also a learning tool for students in applying knowledge to real situations in society.